The Significance of Service The Values of a University - Tan, Betsy Joy B. (Silliman Journal, 2023)
Teaching is service. Nowhere is this service made more profoundly professional than when Values Education was institutionalized in the Philippine educational system. At Silliman University, Values Education is values integration, a curricular design that extends from the classroom to the community. Through a core curricu-lum that provides a cluster of courses within the general education program an-chored on the university’s mission, Silliman University has responded to that call. However, how a student evolves into a social being who is self-actualized with a deep sense of love of country and the world, is the ultimate affirmation of what a university can do to contribute to shaping human excellence—the education of tho mind for academic excellence, the education of emotions for human values, and the education of the conscience for life’s principles of harmonious living.